Economic Growth and Carbon Emissions: Environmental Kuznets Curve (EKC) Hypothesis in Indonesia from 1990 to 2020 - Febriyanto, Aryo Dwi; Panjawa, Jihad Lukis (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2024)
All countries in the world, both developed and developing countries, are facing pollution problems in order to be able to balance accelerating economic growth with environmental degradation problems due to their economic activities. The acceleration of economic development in Indonesia to achieve high industrial growth is directly proportional to the cause of the high increase in carbon dioxide emissions. The purpose of this study is to see the environmental impact of the regulations set, as well as to provide recommendations for the formulation of environmentally friendly economic development policies in the future. This study applies time series data regression with ECM as the method used. Indonesia was chosen as the object of the theory Environmental Kuznets Curve (EKC) from 1990 to 2020. The results of the study show that the squared industry variable in the short term is not significant, but in the long term, it is significant and has an effect of -0.0002, which means that the EKC hypothesis is not proven in the short and long-term, only a decrease in environmental degradation occurs. (CO2 emissions) because industry increases in the long term or industry has a significant negative effect on carbon dioxide emissions in the long term.